A methodological evaluation of the determination of critical oxygen threshold in an estuarine teleost - Negrete, Benjamin (Biol Open, 2019)
One measure of hypoxia tolerance is the critical oxygen threshold, P(crit), which is the point where standard metabolism can no longer be maintained through aerobic processes. Traditionally, P(crit) was determined using closed respirometry, whereby the fish's respiration naturally lowered O(2). More recently, intermittent flow techniques have been adopted, where N(2) is used to displace O(2), which ostensibly reduces end-product build-up. This study used a paired design on the marine teleost, red drum. P(crit) is comparable between closed (4.6±0.2 kPa; mean±s.e.m.) and intermittent flow (4.4±0.2 kPa; mean±s.e.m.) respirometry. pCO(2), ammonia and pH changes within the chamber were measured prior to the onset of P(crit) and at the end of a typical P(crit) trial and revealed changes in water chemistry in both closed and intermittent flow. P(crit) values were similar in both methods of hypoxia induction regardless of subsequent water chemistry changes that occurred in both methods.